2009
DOI: 10.1111/j.1748-1716.2009.01961.x
|View full text |Cite
|
Sign up to set email alerts
|

Tenuifolin, an extract derived from tenuigenin, inhibits amyloid‐β secretion in vitro

Abstract: Tenuifolin is an effective compound from tenuigenin. We believe that this finding should lead the way for future experiments to determine the exact mechanism for tenuifolin's effect on Abeta secretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 24 publications
0
44
0
Order By: Relevance
“…Tenuigenin is the active component from the roots of Polygala tenuifolia Willd and shares many of its effects, such as the facilitation of memory and treatment of agerelated declines in function [22].…”
Section: Discussionmentioning
confidence: 99%
“…Tenuigenin is the active component from the roots of Polygala tenuifolia Willd and shares many of its effects, such as the facilitation of memory and treatment of agerelated declines in function [22].…”
Section: Discussionmentioning
confidence: 99%
“…(Polygalaceae) is commonly used as a traditional Chinese medicine to treat memory loss (Lv et al, 2009). An extract of P. tenuifolia was reported to alleviate scopolamine-induced cognitive impairment in rats (Park et al, 2002).…”
Section: β-Secretase Inhibitorsmentioning
confidence: 99%
“…Recently, P. tenuifolia was reported to provide sedative and anti-dementia neuroprotective efficacy in several in vitro pharmacological studies, as well as anti-oxidative and anti-neurotoxic effects in cultured neurons [14,21,22]. The present study shows that the neuron protective effects of TEN might result from the inhibition of LPS-induced microglial activation and the release of inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 51%
“…In a rat model of Alzheimer's disease (AD), P. tenuifolia root extracts ameliorate spatial cognition disorders and protect neuronal cells against in vitro toxins [18][19][20], as well as improving the cognitive behavior of AD animal models [16]. Cell culture results have shown that treatment with P. tenuifolia decreases secretion of amyloid b-protein, which is responsible for neuronal pathogenesis and cell death in AD [21,22]. BT-11, the extract from P. tenuifolia Willdenow roots, has been shown to ameliorate memory impairment induced by scopolamine and stress in rats [15].…”
Section: Introductionmentioning
confidence: 98%